Pengaruh Penghargaan Terhadap Kepuasan Kerja Dan Komitmen Organisasional - Milia, Milia Astuti; Putri Eka Kusuma Wardani (CV. Satria Jaya, 2024)
This study aims to determine (1) the effect of appreciation on job satisfaction at PT. Raja Indonesia Perkassa Pasuruan, (2) the influence of Awards on Organizational Commitment of PT. Raja Indonesia Perkassa Pasuruan (3) the effect of Job Satisfaction on Organizational Commitment of PT. Raja Indonesia Perkassa Pasuruan. The type of research used in this research is exportative with a quantitative approach. The research objective was to determine the lack of job satisfaction with the company's employees. In this study, the research subjects were employees at PT. Raja Indonesia Perkassa Pasuruan. The objects in this study are rewards, job satisfaction, and organizational commitment. The population in this study were 135 employees and the sample used was 100 employees using the Slovin formula. Data collection techniques in this study using purposive sampling method. Reliability Test, Linerity test in PLS is carried out to determine whether it is significant or not. The results of this study indicate that (1) there is a positive and significant effect of reward on job satisfaction at PT. Raja Indonesia Perkassa Pasuruan path coefficient (β) = 0.964 p value = <0.001 (2) there is a positive and significant effect of appreciation on the organizational commitment of PT. Raja Indonesia Perkassa Pasuruan path coefficient (β) = 0.332 p value = <0.001 (3) there is a positive and significant effect of job satisfaction on organizational commitment of PT. Raja Indonesia Perkassa Pasuruan path coefficient (β) = 0.633 p value = <0.001.